Multicast Path Setup Incorporating Evicting - Hu, Wenmin; Lu, Zhonghai; Liu, Hengzhu; Jantsch, Axel (Elektronika ir Elektrotechnika, 2012)
In this paper, we propose a novel multicast path setup scheme, which incorporates the evicting process. Compared with the previous work, our scheme either overcomes the limitation in evicting times or reduces the setup latency. DOI: http://dx.doi.org/10.5755/j01.eee.18.8.2637